Shedding some light on the dark matter of competition: Insights from the strategic management and organizational science literature for the consideration of diversity aspects in merger review - Benjamin R. Kern; Malte Ackermann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
A merger between two innovation competitors is often suspected to reduce the variety of heterogeneous entities which are currently undertaking R&D or which are well situated to undertake R&D in a certain field. The consequential reduction of diversity can be detrimental to innovation because it reduces the number of independent sources for possible future innovations and might furthermore lead to an alignment of formerly different R&D programs. However, if diversity indeed benefits innovative performance, even merged firms should have an incentive to maintain it in-house. Therefore, this article aims to bring to light whether firms can indeed be expected to create or maintain diversity post-merger. By focusing on the strategic management and organizational science literature we will demonstrate that the creation/maintenance of independent entities is indeed considered as an important determinant for the innovativeness and general performance of firms. Nevertheless, we will also show that this strategy has several grave implementation problems and might be hampered by certain trade-offs. As a consequence, competition authorities cannot presume that a reduced inter-firm diversity will get substituted by an increased intra-firm diversity without fail.
Keywords: B52; K21; L4; M1; O31; O32; 330